Dynamics of the additional professional education of civil servants - Anatoly V. Ivanov; Oleg V. Kuznetsov; S. N. Hursevich (Высшее образование в России)
The article deals with the dynamics of the additional professional education of civil servants,including their retraining, professional development and traineeship. As a method of study there has been used a comparative analysis of the raw data of the State order on retraining, skills upgrading and traineeship of federal public servants over the past five years. The article offers some recommendations on organizational and financial support of additional professional education of civil servants.